Spectrophotometric Analysis of an Antipyretic Drug for Solubillity Determination - Singh, Surya Pratap; ranjitsinh, Gohel kishorsinh; Khinchi, Mahaveer Prasad (Asian Journal of Pharmaceutical Research and Development, 2013)
The solubility of a substance becomes especially important in the pharmaceutical field because it often represents a major factor that controls the bioavailability of a drug substance. Moreover, solubility and solubility-related properties can also provide important information regarding the structure of drug substances, and in their range of possible intermolecular interactions. For these reasons, a comprehensive knowledge of solubility phenomena permits pharmaceutical scientists to develop an optimal understanding of a drug substance, to determine the ultimate form of the drug substance, and to yield information essential to the development and processing of its dosage forms.